Pengaruh Gaya Hidup dan Persepsi terhadap Keputusan Pembelian pada Craveat Healthy Food - Nabila, Nabila; Lestari, Retno Budi (Universitas Multi Data Palembang, 2025)
This study aims to analyze the impact of way of life, and discernment on obtaining choices at Craveat sound nourishment mostly and synchronous impact of way of life, and recognition on acquiring choices. Information collection was conducted through surveys disseminated to 171 respondents. The inspecting method utilized was nonprobability testing with a purposive examining strategy, and the information were analyzed utilizing SPSS 26. The comes about appear that the halfway test (t-test) shows that the factors way of life, and discernment have a positive and signitificant impact on acquiring choices. The concurrent test (F-test) illustrates that the autonomous factors way of life, and discernment collectively have a positive and signitificant impact on the subordinate variable, specifically acquiring choices.